After virus exposure, early bystander naïve CD8 T cell activation relies on NAD+ salvage metabolism - Holay, Namit; Kennedy, Barry E.; Murphy, J. Patrick; Konda, Prathyusha; Giacomantonio, Michael; Brauer-Chapin, Tatjana; Paulo, Joao A.; Kumar, Vishnupriyan; Kim, Youra; Elaghil, Mariam; Sisson, Gary; Clements, Derek; et al. (Frontiers in Immunology, 2023)
CD8 T cells play a central role in antiviral immunity. Type I interferons are among the earliest responders after virus exposure and can cause extensive reprogramming and antigen-independent bystander activation of CD8 T cells. Although bystander activation of pre-existing memory CD8 T cells is known to play an important role in host defense and immunopathology, its impact on naïve CD8 T cells remains underappreciated. Here we report that exposure to reovirus, both in vitro or in vivo, promotes bystander activation of naïve CD8 T cells within 24 hours and that this distinct subtype of CD8 T cell displays an innate, antiviral, type I interferon sensitized signature. The induction of bystander naïve CD8 T cells is STAT1 dependent and regulated through nicotinamide phosphoribosyl transferase (NAMPT)-mediated enzymatic actions within NAD+ salvage metabolic biosynthesis. These findings identify a novel, NAD+-dependent aspect of CD8 T cell activation following virus infection with implications for human health and physiology.